PENGARUH STRATEGI PEMBELAJARAN INKUIRI DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SEJARAH SISWA DI SMA NEGERI I LUBUK ALUNG - Melinda, Cicilia (Edu Research, 2017)
This result be influenced by some factor, among is learning strategy and learning motivation research intended to extent of the effect of :1) Applying of strategy study of question and answer inkuiri in course of higher study result learn history compared to student using conventional study strategy 2) Influence of motivation learn to result learn student history 3) See how is related of applying of strategy study of question and answer inkuiri and motivation learn to result learn student at student history subject. This research type is experiment quasi with model of randomized Control Group Pretes-Postes. Population in this research all class student of XI IPS SMA N 1 Lubuk Alung which enlist at semester 2 school year 2015 / 2016. Sampel taken with chosen Purposive sampling tekhnik so that class of IPS1 with amount of student counted 29 people as experiment class and class of IPS2 with amount of student counted 30 people as control class. At experiment class given by treatment of strategy study of question and answer inkuiri and class control only applying of conventional study strategy. Analysis Tekhnik the used is ANOVA. Type Data is primary data and data of sekunder. Technique data collecting of motivation learn to be conducted by propagating research enquette, while to result of learning in the form of tes in the form of multiplechoice which given is final of study. Result of research indicate that: ( 1) Student using strategy study of higher question and answer inkuiri of result learn him than student which learn to use conventional study strategy which with probability of signifikan (0,001<0,05). ( 2) Student owning higher high motivation of result learn him compared to student owning motivation learn to lower using strategy study of question and answer inkuiri which probability of signifikan (0,005 < 0,05) ( 3) There are related between strategy study of question and answer inkuiri and motivation learn to result learn student history which with probability value (0,165<0,05). Pursuant to result of this research of writer suggest to teachers to be can take care of and also improve motivation learn student one of them by applying study strategy which vary one of them aplying of strategy study of question and answer inkuiri.